Love for the Neighbour as Lived Theology: Beliefs and Practices among Ordinary Christians in India - Suneson, Anita Yadala (The ecumenical review, 2020)
The aim of this article is to identify the theological potential for interreligious relations as embodied in the everyday life of ordinary Christians in South India. The empirical study that underlies the discussion is based on interviews with lay churchgoers and pastors from Pentecostal and mainline Protestant churches in Bangalore. The beliefs they articulate, as well as the practices they carry out in their daily lives, are defined as their lived theology. This is analyzed through the terminological framework of theology in four voices. Interviewees express beliefs that emphasize the superiority of Christianity over other religions and the importance of evangelism. Nevertheless, in everyday life they prioritize respect for religious others and maintenance of relationships with them over sharing an exclusivist message about Christ. Their lived theology emphasizes relatedness across religious boundaries and the priority of showing love for the neighbour in practice.